The Experience of Health Care Workers Infected by Corona Virus Diseases-19 - Siti Rochanah; Irma Nurbaeti (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: The number of health workers on the front lines have been affected by COVID-19 and some of them have been infected by COVID-19 since the outbreak of COVID-19. Understanding healthcare workers experience is important to get their meaning and expression.